PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN MATEMATIKA MENGGUNAKAN SOFTWARE FILMORA PADA MAHASISWA UNIVERSITAS COKROAMINOTO YOGYAKARTA - Putra, Aji Permana; Sarumaha, Yenny Anggreini; Khasanah, Nur Dina Meylaila; Khairiani, Dian (Gemi: Jurnal Penelitian dan Pengabdian, 2023)
In today's learning process, we are required to be able to adapt to the digital world. One of the points to pay attention to is making learning videos. Students in the latest curriculum are required to be creative and produce learning videos. Therefore, it is necessary to carry out training in making learning videos on mathematics subjects with the help of Filmora video editing software to then upload them to the YouTube channel. The implementation of the service is aimed at final (seventh) semester students with the hope that when they graduate and finish studying and enter the world of work in the education sector, they will be equipped with optimal abilities, one of which is being able to produce learning videos. The first thing that the service lecturer does is observe students who will be given training, specifically students in the seventh semester of the Mathematics Education study program by giving pre-tests and post-tests. From the pre-test results, it is known that before the treatment (training) was carried out, the value of understanding learning videos was 30%, understanding the use of learning video software 20% and understanding channels for uploading learning videos on the internet 30%. After training and making learning videos, student understanding increased to 70% for learning videos, 60% for learning video software, and 70% for uploading learning videos on the internet. It is hoped that activities like this will be carried out regularly in order to provide education and enlightenment to parties who need it.